1996
DOI: 10.1016/s0006-3495(96)79444-4
|View full text |Cite
|
Sign up to set email alerts
|

Elementary events underlying voltage-dependent G-protein inhibition of N-type calcium channels

Abstract: Voltage-dependent G-protein inhibition of N-type calcium channels reduces presynaptic calcium entry, sharply attenuating neurotransmitter release. Studies in neurons demonstrate that G-proteins have multiple modulatory effects on N-type channels. The observed changes may reflect genuine complexity in G-protein action and/or the intricate interactions of multiple channels and receptors in neurons. Expression of recombinant M2-muscarinic receptors and N-type channels in HEK 293 cells allowed voltage-dependent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
3
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 47 publications
10
122
3
1
Order By: Relevance
“…It has also been proposed that Ca V 2.2 channels inactivate preferentially from intermediate closed state(s) favored during trains of brief depolarizing pulses. 71 If Gβγ were to reduce the probability that the channels populate this state (from which inactivation is preferred) it might reduce the cumulative inactivation throughout a stimulus train. Ca 2+ -dependent inactivation is mediated by calmodulin bound to the C-terminus of the channel α 1 subunit.…”
Section: Subunits-functional Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been proposed that Ca V 2.2 channels inactivate preferentially from intermediate closed state(s) favored during trains of brief depolarizing pulses. 71 If Gβγ were to reduce the probability that the channels populate this state (from which inactivation is preferred) it might reduce the cumulative inactivation throughout a stimulus train. Ca 2+ -dependent inactivation is mediated by calmodulin bound to the C-terminus of the channel α 1 subunit.…”
Section: Subunits-functional Effectsmentioning
confidence: 99%
“…Upon membrane depolarization, the delay before the channel first opens (latency) was increased during inhibition (i.e., the channels were "reluctant" to open), but there was little impact on other single channel parameters. 51,71 Thus, the inhibited channels appeared essentially silenced, unable to open until Gβγ dissociated and the channels shifted to the "willing" state. However, two other studies reported that very brief channel openings from the "reluctant" state can occur in N-type channels (i.e., without Gβγ unbinding), although the probability of such events was low.…”
Section: Subunits-functional Effectsmentioning
confidence: 99%
“…Because GPCRs inhibit Ca 2ϩ channels in a voltage-dependent manner (13,(31)(32)(33)(34), PTX could potentially enhance ER by abolishing this block. We measured presynaptic Ca 2ϩ currents derived from the excitatory nerve terminal current (ENTC) (7,8,35).…”
Section: Ptx Increases Glu Sr and Er And Alters Its Time Course Presmentioning
confidence: 99%
“…Activation of voltage-gated sodium channels is initiated by the outward movement of positive gating charges in the S4 segments in each domain under the influence of the transmembrane electric field (35)(36)(37)(38)(39). Shift of N-type Ca 2ϩ channels to the reluctant gating mode by G protein modulation slows the gating current caused by outward movement of the S4 voltage sensors preceding channel activation (40,41), as if the outward movement of one or more S4 segments is slowed by G␤␥ binding. Peptide neurotoxins alter sodium channel gating by binding to the S3-S4 loop at the extracellular end of the voltage-sensing S4 segments and altering their transmembrane movement by voltage-sensor trapping (42,43).…”
Section: A Voltage Sensor-trapping Mechanism For G Protein Modulation Ofmentioning
confidence: 99%